2015
DOI: 10.1016/j.ejrad.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound molecular imaging: Moving toward clinical translation

Abstract: Ultrasound is a widely available, cost-effective, real-time, non-invasive and safe imaging modality widely used in the clinic for anatomical and functional imaging. With the introduction of novel molecularly-targeted ultrasound contrast agents, another dimension of ultrasound has become a reality: diagnosing and monitoring pathological processes at the molecular level. Most commonly used ultrasound molecular imaging contrast agents are micron sized, gas-containing microbubbles functionalized to recognize and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
175
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 66 publications
1
175
0
1
Order By: Relevance
“…In contrast, we found that the expression of the pro-angiogenic marker proteins VEGFR-2 and α v ß 3 integrin differed significantly between breast cancer, pre-invasive cancerous lesions and benign breast lesions. In line with preclinical studies, our histopathological in situ findings support the notion that VEGFR-2 and α v ß 3 integrin may be suitable molecular imaging targets for tumor diagnosis and characterization in the breast [5,6,[10][11][12][23][24][25].…”
Section: Endothelial Vegfr-2 Levels But Not Vascular Area Fractionssupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, we found that the expression of the pro-angiogenic marker proteins VEGFR-2 and α v ß 3 integrin differed significantly between breast cancer, pre-invasive cancerous lesions and benign breast lesions. In line with preclinical studies, our histopathological in situ findings support the notion that VEGFR-2 and α v ß 3 integrin may be suitable molecular imaging targets for tumor diagnosis and characterization in the breast [5,6,[10][11][12][23][24][25].…”
Section: Endothelial Vegfr-2 Levels But Not Vascular Area Fractionssupporting
confidence: 71%
“…S4+5). [5,6,[10][11][12][23][24][25]. However, besides a pilot phase study on breast cancer patients using radiolabeled α V ß 3 -targeted RGD peptides and PET demonstrating a significant probe uptake in the primary lesion and in the metastases [19], clinical studies comparing the diagnostic power of functional vs. molecular imaging for differentiating (mammographically) suspect tumors or for monitoring recurrent lesions upon breast cancer surgery have not yet been reported.…”
Section: Endothelial Vegfr-2 Levels But Not Vascular Area Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most successful of these is the BR55, which targets VEGFR and has been reported in tumor diagnosis and evaluations of anti-vascular therapy. 34,35 In the ultrasound molecular imaging of tumor parenchyma, targeted ultrasound microbubbles at the micron scale cannot penetrate tumor blood vessels to enter tumor tissues; therefore, there are fewer relevant studies on the direct specific binding between ultrasound microbubbles and tumor cells to achieve targeted imaging.…”
mentioning
confidence: 99%
“…14.15. The physical system formed by the capsule, the oil and the surrounding water obeys the following set of equations: 5) with the substitutionT = rT , as before. In the equations, the subscript p refers to the polymer, w to the water and oil to the oil.…”
Section: Methodsmentioning
confidence: 99%